2010
DOI: 10.2174/187221410790226756
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Antihypertensive Drug Use on Bone Mineral Density and Osteoporotic Fracture - From an Epidemiological Perspective

Abstract: Osteoporosis, a common disease today, has serious impacts on both patients and society, because prognosis can be complicated and therapy costly. It is therefore important to identify risk factors for osteoporosis to ensure the prevention and early detection. Adjustment of confounding factors is important for accurate evaluation of risk factors. In societies with long average life spans, the number of people with multiple chronic diseases has increased in recent years, resulting in many reports of secondary ost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 78 publications
(115 reference statements)
0
1
0
Order By: Relevance
“…Some studies have also found an increased loss of BMD from the skeleton with high blood pressure [15,18,21]. Hypertensive patients may be more prone to fall injuries such as fractures as a result of decreased baroreflex sensitivity [22,23].…”
Section: Hypertension and Fracture Riskmentioning
confidence: 99%
“…Some studies have also found an increased loss of BMD from the skeleton with high blood pressure [15,18,21]. Hypertensive patients may be more prone to fall injuries such as fractures as a result of decreased baroreflex sensitivity [22,23].…”
Section: Hypertension and Fracture Riskmentioning
confidence: 99%